2000
DOI: 10.1016/s0921-4534(00)00383-x
|View full text |Cite
|
Sign up to set email alerts
|

A Fermi liquid model for the overdoped and optimally doped cuprate superconductors: scattering rate, susceptibility, spin resonance peak and superconducting transition

Abstract: We present a Fermi liquid model for the overdoped and optimally doped cuprate superconductors. For the normal state, we provide an analytic demonstration, backed by self-consistent Baym-Kadanoff (BK) numerical calculations, of the linear in temperature resistivity and linear in 1/energy optical conductivity, provided the interacting Fermi liquid has strong peaks in its density of states (van-Hove singularities in 2 dimensions) near the chemical potential µ. Recent ARPES expts. by Valla et al., Science 285, 211… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 55 publications
5
45
0
Order By: Relevance
“…The observation of a NFL behavior without quantum critical point in both Co-doped and V-doped LiFeAs is consistent with a recent theoretical study emphasizing on the impact of nesting on the temperature evolution of the electrical conductivity [24]. We caution though that the linear resistivity in the cuprates was previously derived in the context of a FL with a large density-of-states (like a van Hove singularity) near E F [25,26], a condition that also applies to Fe-based superconductors near good nesting conditions. As shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The observation of a NFL behavior without quantum critical point in both Co-doped and V-doped LiFeAs is consistent with a recent theoretical study emphasizing on the impact of nesting on the temperature evolution of the electrical conductivity [24]. We caution though that the linear resistivity in the cuprates was previously derived in the context of a FL with a large density-of-states (like a van Hove singularity) near E F [25,26], a condition that also applies to Fe-based superconductors near good nesting conditions. As shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Our treatment shows that ω B here is nothing else but the fermionic energy w k−qo ,ǫ . The results here complement our earlier normal state results in 3,4 . ARPES experiments 10,11 have indicated that in the superconducting state, and, presumably, for ǫ → 0, the scattering rate is linear in T for k F close to the nodal directions, but otherwise saturates to a value which increases as k F approaches the vH points.…”
supporting
confidence: 91%
“…The normal state result was obtained in 3,4 . Summarizing, within the Fermi liquid Eliashberg formalism, we calculate the one-particle scattering rate in the superconducting state of overdoped cuprates.…”
mentioning
confidence: 96%
See 2 more Smart Citations